The Production, Survival, and storage study of Freeze and spray dried Lactococcus lactis using whey as protectant: Preparation of Freeze and spray drying of Lactococcus lactis using whey based medium - Vandna, Dr Vandna; Narendra Kumar; Surajit Mandal; Subrota Hati (Indian Journal of Dairy Science, 2023)
The present research was hypothesized that preservation of bacterial cell with higher viability by drying methodologies is a challenging process as L. lactis ssp. lactis, is heat sensitive bacteria. Thus, drying conditions must be mild enough to avoid damaging them but sufficiently efficient to yield a powder with moisture content below 4%, which is desirable for storage stability. To overcome the lack of moisture sweet whey was used as protective medium for freeze and spray drying of L. lactis ssp. lactis. The present study was designed to evaluate the survival and storage stability of freeze and spray dried Lactococcus lactis ssp. lactis, using sweet whey as protective medium up to 90 days at -20°C storage temperature. The percent survivability for freeze and spray dried powders of Lactococcus lactis ssp. lactis was found 60% and 36% respectively. A significant decrease of more than one log count for freeze dried culture and two log count decrease in case of spray dried culture powder was observed after 90 days of storage period. The moisture content and storage temperature played a crucial role in storage stability of both the powders, which was observed within the acceptable limit. the present study culminates that storage temperature and moisture content of bacterial powders are the key factors influencing its viability. In addition, higher survivability and storage stability of freeze-dried powder (60%) as compared to spray dried bacterial cells (36%) develops new technological route to improve cell survivability by spray drying and further during storage.